2023
DOI: 10.1155/2023/6976389
|View full text |Cite
|
Sign up to set email alerts
|

The Cut-Off Value of Serum Anti-Müllerian Hormone Levels for the Diagnosis of Turner Syndrome with Spontaneous Puberty

Abstract: Objective. Preservation of fertility in Turner syndrome (TS) patients may be feasible through cryopreservation of ovarian tissue before follicles begin to disappear. Anti-Müllerian hormone (AMH) is said to be a predictive factor of spontaneous pubertal development in TS. We aimed to determine the cut-off values of AMH for the diagnosis of TS girls with spontaneous puberty. Design and methods: A total of 95 TS patients between 4 and 17 years were evaluated at the Department of Pediatric Genetic Metabolism and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In the study of Hagen et al (2010a ) all girls with AMH <0.56 ng/ml did not develop spontaneous thelarche. Moreover, AMH-levels were correlated with karyotype, as described by Wang et al (2023) , who found significant higher levels of AMH in young girls with 45,X/46,XX aged 4–7 years, compared to girls with 45,X and ‘other’ karyotypes (median values respectively 1.13 ng/ml vs 0.02 and 0.04 ng/ml).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…In the study of Hagen et al (2010a ) all girls with AMH <0.56 ng/ml did not develop spontaneous thelarche. Moreover, AMH-levels were correlated with karyotype, as described by Wang et al (2023) , who found significant higher levels of AMH in young girls with 45,X/46,XX aged 4–7 years, compared to girls with 45,X and ‘other’ karyotypes (median values respectively 1.13 ng/ml vs 0.02 and 0.04 ng/ml).…”
Section: Resultsmentioning
confidence: 83%
“…In addition, according to the findings of Hankus et al (2018) , the probability of experiencing spontaneous menarche when FSH levels exceeded 6.7 IU/l at the age of 6–10 years, was observed to be reduced. In most girls, FSH remained low during childhood, and in these cases AMH appears to be the most reliable indicator for ovarian reserve ( Hagen et al , 2010a ; Purushothaman et al , 2010 ; Kallio et al , 2012 ; Visser et al , 2013 ; Lunding et al , 2015 ; Wang et al , 2023 ). Lunding et al (2015) reported on pubertal development and AMH levels before pubertal onset in a longitudinal observational cohort study that included 15 girls with TS.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation